Strategic Timing in Financial Markets: Real Options Analysis of American Options - Gilles Tamba Bokolo; Ngoyi Landu Tresor; Mabela Rostin; Rebecca Omana Walo (Ratio Mathematica, 2024)
This paper delves into the nuanced realm of option pricing, focusing specifically on American call and put options within the framework of real options analysis. Traditional models often struggle to account for the complex decision-making process inherent in American options due to their early exercise feature. Leveraging the flexibility offered by real options methodology, this paper explores the optimal stopping time, a critical determinant in option pricing. Through a rigorous analytical approach and Monte Carlo simulations, we unveil explicit expressions for the optimal stopping time and option values. By bridging theory with practical application, this research offers valuable insights into the dynamics of American options and their pricing in real-world financial markets.